2021
DOI: 10.3390/ijms22084048
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant IGF-1 Induces Sex-Specific Changes in Bone Composition and Remodeling in Adult Mice with Pappa2 Deficiency

Abstract: Deficiency of pregnancy-associated plasma protein-A2 (PAPP-A2), an IGF-1 availability regulator, causes postnatal growth failure and dysregulation of bone size and density. The present study aimed to determine the effects of recombinant murine IGF-1 (rmIGF-1) on bone composition and remodeling in constitutive Pappa2 knock-out (ko/ko) mice. To address this challenge, X-ray diffraction (XRD), attenuated total reflection-fourier transform infra-red (ATR-FTIR) spectroscopy and gene expression analysis of members o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 81 publications
4
23
0
Order By: Relevance
“…In contrast, when specific Pappa2 deletion was triggered at 20 weeks of age by tamoxifen-induced Cre -mediated recombination (resulting in whole body Pappa2 deletion), no difference between genotypes in body weight was detected [ 69 ]. Recently, using the second mouse model for constitutive Pappa2 deletion, our research group also reported a sex-independent reduction in body length of Pappa2 KO mice at 8 months of age [ 70 ]. A constitutive knock-in mouse model employing the human p.Ala1033Val mutation in PAPP-A2 was generated using the CRISPR/Cas9 system [ 67 ].…”
Section: Papp-a2 Mouse Models: What Are We Learning?mentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, when specific Pappa2 deletion was triggered at 20 weeks of age by tamoxifen-induced Cre -mediated recombination (resulting in whole body Pappa2 deletion), no difference between genotypes in body weight was detected [ 69 ]. Recently, using the second mouse model for constitutive Pappa2 deletion, our research group also reported a sex-independent reduction in body length of Pappa2 KO mice at 8 months of age [ 70 ]. A constitutive knock-in mouse model employing the human p.Ala1033Val mutation in PAPP-A2 was generated using the CRISPR/Cas9 system [ 67 ].…”
Section: Papp-a2 Mouse Models: What Are We Learning?mentioning
confidence: 99%
“…In contrast, increased circulating levels of Igfbp3 and Igfals were found in Pappa2 KI mice at 4 months of age [ 67 ]. We found a genotype effect on Igfbp3 mRNA levels in the bone of 8-month-old Pappa2 KO mice with female Pappa2 KO mice having higher Igfbp3 mRNA levels in the tibia than female WT littermates [ 70 ].…”
Section: Papp-a2 Mouse Models: What Are We Learning?mentioning
confidence: 99%
See 2 more Smart Citations
“…Loss-of-function mutations in the human PAPPA2 gene cause short stature and reduced bone density [ 34 , 35 ], and these conditions are improved by treatment with IGF-I [ 36 38 ]. In mice, deletion of Pappa2 reduces the linear growth of bones [ 39 41 ] and affects bone composition and microarchitecture [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%